2015
DOI: 10.18632/oncotarget.3171
|View full text |Cite|
|
Sign up to set email alerts
|

Aspirin counteracts cancer stem cell features, desmoplasia and gemcitabine resistance in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is characterized by an extremely poor prognosis. An inflammatory microenvironment triggers the pronounced desmoplasia, the selection of cancer stem-like cells (CSCs) and therapy resistance. The anti-inflammatory drug aspirin is suggested to lower the risk for PDA and to improve the treatment, although available results are conflicting and the effect of aspirin to CSC characteristics and desmoplasia in PDA has not yet been investigated. We characterized the influence of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 42 publications
3
71
0
Order By: Relevance
“…Aspirin has been shown to inhibit colony formation, SR capacity by spheroid-formation assay and tumor growth in a nude mouse xenograft model in breast and pancreatic cancer (25,26). Our present long-term suspension culture, however, enables us to express the SR capacity of blast progenitors as rSLP, compare each rSLP for different agents alone and in combination, and uncover the growth-regulatory mechanisms by adding stimulators or inhibitors to the culture.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has been shown to inhibit colony formation, SR capacity by spheroid-formation assay and tumor growth in a nude mouse xenograft model in breast and pancreatic cancer (25,26). Our present long-term suspension culture, however, enables us to express the SR capacity of blast progenitors as rSLP, compare each rSLP for different agents alone and in combination, and uncover the growth-regulatory mechanisms by adding stimulators or inhibitors to the culture.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia also results in the accumulation of lactate dehydrogenase-A, which assists in the maintenance of the hypoxic phenotype and increasing chemoresistance (11). Novel molecular targets and molecules that have been identified include: Protein tyrosine kinase-6 (12); vitamin D receptor (VDR) (13); mucin-1 (MUC1) (14); ormeloxifene that targets the sonic hedgehog pathway (15); sodium metaarsenite (KML001) that targets the epidermal growth factor receptor (EGFR) and matrix metalloproteinase (MMP) 2 (16); the quinazolinedione-based redox modulator QD232 that targets proto-oncogene tyrosine-protein kinase/focal adhesion kinase (FAK) and signal transducer and activator of transcription 3 phosphorylation (17); aspirin, which was revealed to reduce tumor growth and sensitize cells to gemcitabine (18); the curaxin CBL0137, which targets NF-κB and ribonucleotide reductase (19) and sepantronium bromide (YM155) (20)(21)(22), which inhibits the action of inhibitor of apoptosis protein family members (20), as summarized in Table I.…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…In recent studies ,aspirin beside having anti-inflammatory, anti-pyretic effects via irreversible inactivation of both cycloxygenase(COX) 1 and 2 enzyme in multiple observational studies and controlled randomized trial has also shown promise to be effective as chemopreventive agent like in cancer of prostate, breast, pancreatic and colon either in its original or as modified form [116][117][118][119][120][121].…”
Section: Aspirinmentioning
confidence: 99%